Analytical Dashboard for Air Quality Monitoring in Lisbon - Forte, André Miguel Afonso (2024)
Nowadays, air pollution is one of the main concerns of the policymakers and tracking the pollutants’ concentrations in the atmosphere emerged as a necessity. Due to that, a lot of mechanisms have been implemented to monitor the quality of the air that we breathe, studying what are the main sources of the pollutants and their effect on human health. Since traffic is one of the main contributors to the gases’ emissions, studying the impact of its volume on air pollutants concentration is extremely relevant because it might contribute to the application of policies that aim to reduce pollution in the atmosphere. For that reason, the present study focuses on developing a framework that monitors the air concentration and traffic congestion indicators of Lisbon between 2021 and 2023. Moreover, the solution provides information about the evaluation of the quality of Lisbon air, making a comparison with the European Commission criteria. The interactive Dashboard allows temporal and spatial analyses and the users may personalize the information regarding their own personal study objectives. Also, the framework crosses air pollution and traffic data in a descriptive analysis, exploring their influence and exposing insights that are relevant in the Air Pollution research field.